Response and Side Effects from Rheumatoid Arthritis Therapy at Dr. Soetomo General Hospital Surabaya 2017 - Ayu Imamatun Nisa; Awalia Awalia; Jusak Nugraha (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2022)
Introduction: Rheumatoid arthritis (RA) is an autoimmune disease which mainly attacks synovial membrane and causes systemic manifestation. During treatment, controlling disease activity is needed to prevent further complication. On the other hand, medications used in the treatment of RA may bring various side effects. It is important to evaluate side effects from the given therapy.Methods: This study aimed to evaluate response and side effects of therapy in RA patients. The samples were collected from 59 RA patients at Rheumatology Division of Outpatient Clinic in Department of Internal Medicine Dr. Soetomo General Hospital Surabaya in 2017. This study method was descriptive observational with cross sectional design using medical records.Results: Pain was reduced in 83.1% patients, Erythrocyte Sedimentation Rate (ESR) increased in 61.4% patients, and C-Reactive Protein (CRP) decreased in 50% patients. Based on the statistic analysis, ESR decreased significantly (p = 0.012) while CRP decreased not significantly (p = 0.415). The side effects were observed from clinical and laboratory data. Based on clinical symptoms, there were alopecia in 1.7% patient, dyspepsia in 78% patients, infection in 27.1% patients, and other symptoms including itchy skin, neuropathy, hyperuricemia, hyperkalemia and Acute Kidney Injury (AKI). Meanwhile, abnormalities in laboratory data include increased aspartate transaminase (AST) in 3.8% patients, increased alanine transaminase (ALT) in 26.1% patients, increased Blood Urea Nitrogen (BUN) in 7.9% patients, increased creatinine serum in 7.9% patients, decreased hemoglobin in 15.5% patients, and decreased leukocytes in 3.4% patients.Conclusion: Most patients had a good therapeutic response based on decreased pain, while ESR had a significant decrease and CRP did not have significant decrease. Side effects discovered in patients were various